16 JURUS PENULISAN JURNAL - Zahar, Iwan; Pertiwi, Ratih; Marwan, Rudi Heri (Universitas Esa Unggul, 2021)
Journal writing, particularly international journal writing, is fraught with difficulties, and just a handful Esa Unggul University authors have been accepted into prestigious publications. The goal of this document is to assist authors, researchers, and lecturers in determining the best writing technique for breaking into these publications. Survey quest was used to determine whether or not the trainees had grasped the material. The technique for determining if the training was understood was to ask 51 Esa Unggul lecturers survey questions. This course will cover 16 different approaches to construct journals, including 1) journal selection. 2) Downloads of journals 3) Before being directed to the desired journal, examine and read many journals. 4) Citations account for 80% of the total, whereas books account for 20% 4) Citations account for 80% of the total, whereas books account for 20%. 5) There should be at least 20 references, and no more than 30% of the references should be cited. 6) Citation of the most recent and highest-ranking journals, from well-known and legitimate publishers, as well as well-known authors like Foucault and others. 7) Identification of issues that occur as a result of reading the journal 8) Decide on research methods 9) Choose a title (2 W + 1 H) 10) Read the journal's writing rules and, most crucially, the journal's writing style. 11) the structure of the writing 12 Pay attention to the manner of writing 13) the significance of keywords, abstracts, and the problem's background 14) the selection of Scopus and international journal rankings 15) evaluation by peer groups 16) English interpreter Keywords: scopus, international journals, writing style